2021
DOI: 10.1186/s12998-021-00405-1
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive study of sports chiropractors with an International Chiropractic Sport Science Practitioner qualification: a cross-sectional survey

Abstract: Background This paper describes the education and case management profile of sports chiropractors with the Federation of International Sports Chiropractors (FICS) postgraduate qualification: International Chiropractic Sport Science Practitioner (ICSSP). The ICSSP is the predominant international sports chiropractic qualification. Methods A cross-sectional survey, carried out between 22/10/2014 and 22/12/2014,was utilized with a 39-item web-based s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Many participants described that their sports chiropractor took the time to identify the cause of their problem, which sometimes involved addressing their sports technique or injury mechanism, and often involved evaluating and treating areas distant to the injured site to improve their overall body mechanics. Our qualitative data support previous self-report surveys characterizing sports chiropractic practice that reported the frequent use of multi-modal care interventions [ 20 – 23 ], the treatment of the extremities [ 21 – 23 ], and treatment intentions to improve sport performance [ 22 , 23 ]. While providing musculoskeletal assessment and treatment including at and beyond the injury site, this approach to care is not unique to sports chiropractors.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Many participants described that their sports chiropractor took the time to identify the cause of their problem, which sometimes involved addressing their sports technique or injury mechanism, and often involved evaluating and treating areas distant to the injured site to improve their overall body mechanics. Our qualitative data support previous self-report surveys characterizing sports chiropractic practice that reported the frequent use of multi-modal care interventions [ 20 – 23 ], the treatment of the extremities [ 21 – 23 ], and treatment intentions to improve sport performance [ 22 , 23 ]. While providing musculoskeletal assessment and treatment including at and beyond the injury site, this approach to care is not unique to sports chiropractors.…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, the use of physical and complementary therapies has been reported to be a part of competitive athletes’ lifestyle practices [ 19 ]. It has been suggested that sports chiropractic care may differ from the care provided by general practice chiropractors, with self-report data revealing chiropractors with sports qualifications more often utilize a multimodal approach [ 20 – 23 ], frequently treat extremity conditions [ 21 – 23 ], and apply interventions with the intent to improve sports performance [ 23 ]. Despite these reports, clinical evidence of these defining characteristics of sports chiropractic practice has not been directly investigated, and it is not known how athletes perceive and experience the care provided by sports chiropractors.…”
Section: Introductionmentioning
confidence: 99%
“…Establishing chiropractic clinics and centers that cater to the needs of athletes and the general population is a crucial step in this process. These facilities should be outfitted with cutting-edge diagnostic and treatment equipment, thereby enabling chiropractors to provide evidence-based, high-quality care [ 40 ].…”
Section: Reviewmentioning
confidence: 99%
“…El Quiropráctico en el deporte debe basar su práctica en evidencia, así como reconocer la importancia del manejo multidisciplinario junto con otros profesionales para lograr favorecer de manera conjunta los intereses del deportista (Hoskins, et, al. 2009;Nelson, et, al. 2021).…”
Section: Introductionunclassified